Some Issues of Integrated Teaching of Fundamental Sciences in Higher Technical Education - Khimmatkulov, Odilbay (European Journal of Life Safety and Stability (2660-9630), 2022)
Some issues of teaching fundamental natural sciences with the help of integrative technologies in higher technical educational institutions are highlighted. Within the framework of physical science, there are opportunities to explain some phenomena through general approaches, laws and imaginations. As a result of an integrative and systematic approach to the study of natural phenomena, the knowledge obtained by students will be complete and perfect, it is emphasized that it is possible to ensure the growth of their creative abilities.